PSYCHOLOGICAL WELL-BEING AND SPIRITUAL INTELLIGENCE AS PREDICTORS OF SUICIDAL IDEATION AMONG EMERGING ADULTS IN MALAYSIA - Foo Suh Jin; Lo Kah Wah; Wirawahida Kamarul Zaman; Sanggari Krishnan; Komathi Lokithasan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Suicide behavior is one of a worrisome issue not only in Malaysia but all over the world. The World Population Review and Statista in 2019 reported suicide case in Malaysia was 5.5 per 100,000 inhabitants in 2016 and showed an increasing pattern for the past three years(WHO,2018) revealed that most of the suicide cases lead to mortality were came from the age of 15 to 29 years old. The current study aims to explore the suicidal ideation issue of emerging adults between the age of 18 to 25 years old. During this period, they may face many challenges such as searching for self-identity, instabilities of life, and sudden loss of life direction due to no or few obligation and commitment to others, which may have an impact towards their psychological health (Eccles, Templeton, Barber, & Stone, 2003). Therefore, the objective of this study is to identify the relationship between psychological well-being and spiritual intelligence and suicidal ideation among emerging adults in Malaysia. A total of 304 samples were recruited, but only 271 samples had completed the questionnaires, which was collected through the online and paper-and-pencil method. The Scale of Suicidal Ideation (SSI), Ryff’s Psychological Well-Being Scale-42 items, and Spiritual Intelligence Self-Report Inventory-24 items were used to measure all variables in this study. Data collected was calculated using the Statistical Package for Social Science (SPSS) software version 25.0. Results of Pearson correlation showed that there was a significant negative correlation between psychological well-being and suicidal ideation while a significant positive correlation between spiritual intelligence and suicidal ideation. Results of multiple linear regression found out psychological well-being, and spiritual intelligence statistically predicted suicidal ideation. Spiritual intelligence is the best predictor to suicidal ideation. Implications and limitations of this study were discussed, and recommendations for future studies were made.